Effectiveness of first-line abiraterone versus enzalutamide among patients ≥80 years of age with metastatic castration-resistant prostate cancer: A retrospective propensity score–weighted comparative cohort study. (July 2021) - Soleimani, Maryam; Zou, Kevin; Sunderland, Katherine; Struss, Werner; Eigl, Bernie J.; Nappi, Lucia; Kollmannsberger, Christian K.; Finch, Daygen; Noonan, Krista; Vergidis, Joanna; Zulfiqar, Muhammad; Chi, Kim N.; et al.
Abstract: Background: Metastatic castration-resistant prostate cancer (mCRPC) disproportionately affects the elderly. There is limited data assessing the efficacy and tolerability of abiraterone acetate (AA) versus enzalutamide in this population. Objective: To compare the clinical efficacy and tolerability of AA versus enzalutamide in patients ≥ 80 years with mCRPC. Design, setting and participants: A retrospective propensity-weighted comparative cohort study of first-line AA versus enzalutamide among patients with mCRPC aged ≥80 years. Outcome measurements and statistical analysis: Inverse probability treatment weights based on propensity scores were generated to assess the treatment effect of AA versus enzalutamide on time to PSA progression (TTPP), time to progression (TTP) (first of PSA/radiographic/clinical progression) and overall survival using a weighted Cox proportional hazards model. PSA response rate (PSA RR) was compared between groups using Χ 2 . Results and limitations: One hundred fifty-three patients received AA, and 125 received enzalutamide. Enzalutamide was associated with higher PSA RR (61.6% vs 43.8%, P  <  0.004 ), and TTP (hazard ratio [HR] 0.66, 95% confidence interval [CI] 0.50–0.88, P  =  0.01 ) but not TTPP (HR 0.73, 95% CI 0.53–1.01, P  =  0.06 ). There were significantly more dose reductions with enzalutamide (22.9% vs 44.8%, P  >  0.001 ) but there was no interaction between median proportion of full dose received and TTPP or TTP for either drug. Rates of treatment discontinuation (for reasons other than progression) were also significantly different between AA and enzalutamide (28.8% vs 40.8%, respectively, P  =  0.04 ). The most common reason for dose reductions and discontinuation of enzalutamide was fatigue (30.4% and 5.6%, respectively). Conclusions: Despite more dose reductions and a higher treatment discontinuation rate, enzalutamide was associated with a higher PSA RR and longer time to progression, than AA. Given that clinical outcomes were not adversely impacted by decreased treatment exposure, dose modification may be a useful treatment strategy to balance toxicity and tolerance. Highlights: Enzalutamide was associated with more dose reduction 2° toxicity in very elderly. Enzalutamide associated with better PSA response rate and time to any progression. Treatment exposure did not impact outcomes for enzalutamide or abiraterone acetate. Dose reduction on enzalutamide associated with a longer time to any progression. There was no difference in overall survival between treatments.